Pengaruh Kelelahan, Beban Jerja dan Kompetensi Perawat Terhadap Kinerja Perawat - Rusmawati Rusmawati; Sentot Imam Suprapto; Joko Prasetyo (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Hospitals often have difficulty in accurately assessing the performance of a nurse. One of the ways taken by hospitals in improving the performance of their nurses, for example, is through education, training to improve nurse competence, providing appropriate compensation, providing workload, and creating a conducive work environment. The success or failure of a nurse in working will be known if the hospital concerned implements a performance appraisal system. The purpose of this study was to analyze the effect of job fatigue, workload and competence on nurse performance at RSUD Tora Belo. This research is quantitative in nature using multiple linear regression tests. Samples were collected by proportional simple random sampling, totaling 104 respondents. The statistical test results showed that nurses' work fatigue did not affect nurses' performance with a p value = 0.425 > 0.05, workload affected nurses' performance with a p value = 0.19 < 0.05, and nurses' competence did not affect nurses' performance with a p value = 0.354 > 0.05. The results of this study indicate that the workload variable greatly affects the performance of nurses at Tora Belo Hospital, while the variables of fatigue and nurse competence do not show any influence on the performance of nurses at Tora Belo Hospital. Keywords: fatigue, workload, nurse competence, nurse performance